HERO digital platform for Help services: a conceptual and enhanced business model - Ahmad Dahlan, Abdul Rahman; Mohd Murtadza, 'Afifah; Che Saufi, Nurul Nadia (IEEE, 2018)
Just like how UBER challenged the traditional taxi business, HERO is a conceptual business model that aims to challenge and disrupt the existing main agency industry. HERO seeks to provide a non-permanent help-out service for busy people as well as producing side-incomes for anyone that is interested in becoming a helper. An example of a help-out request would be washing dirty clothes, which is capable to be done by almost everyone. Using a portal and mobile application as its platforms, this business promises mobility and ease of use. Helpers, in this business model, is known as Heroes. This is a psychological approach to attract people to register as helpers and for the customers to respect their helpers and do not treat them like slaves. This business uses a rating system to rank the helpers and customers. The higher the ranking, the better is the rating. Ratings can be increased by accepting job requests and given good reviews by customers. Beside Customers and Helpers, this business model also targets volunteers, donors and service provider companies as its potential customer segments.